Law Amending and Supplementing a number of articles of the Law on Military Service Duty - The National Assembly (1994)
This Law amends and supplements a number of articles of the Law on Military Service Duty passed by the National Assembly of the Socialist Republic of Vietnam on the 30th of December 1981, and amended and supplemented on the 21st of December 1990